A produção textual de alunos surdos sob a mediação de softwares educativos - Lopes, Ligiane de Castro (2006)
The reading and writing process experienced by deaf students involves knowledge in two different languages: Sign Language and Portuguese. The differences between these languages and the lack of significant experiences with writing at school are variables which can make the reading and writing learning a hard process to those students. Besides most of their texts are misinterpreted because of the specifications they present. In this work, I aim to analyze the writing of two deaf adults, what motivated me to think about activities that were directed to textual production and, at the same time, could be motivating to the subjects of the research. With this intention, I used computer and image as supports. The analysis of the texts was carried out based in the following parameters: the narrative structure of the texts and the use of cohesive devices as connectives and reference. As results, I verified that there were differences among the texts of the subjects – what I related to the fact that, throughout their lives, they went through different experiences with Sign Language and with Portuguese. Moreover I realized that, even with the difficulties the subjects presented in Portuguese, their texts brought together several characteristic elements of that language such as: the presence of connectives (prepositions, conjunctions) and reference which contribute to textual cohesion.